The Impact of Pharmacist Counseling on Quality of Life in Outpatients with Type 2 Diabetes Mellitus - Hasnidar, Hasnidar; Dian Ratih L; Yati Sumiyati (Sean Institute, 2025)
Type 2 Diabetes Mellitus is a chronic disease that requires long-term management and can reduce a patient's quality of life if not optimally managed. One effort that can be made to improve patient quality of life is through pharmacist counseling, which emphasizes medication education, increased therapy adherence, and the adoption of a healthy lifestyle. This study aims to determine the effect of pharmacist counseling on the quality of life of outpatients with Type 2 Diabetes Mellitus at Bhakti Kartini Hospital. This study used a quasi-experimental design with a pre-test and post-test approach. The study subjects were divided into two groups: an intervention group that received pharmacist counseling and a control group that did not receive counseling. Sampling was conducted using a purposive sampling method on 126 respondents, consisting of 63 patients in each intervention group and 63 patients in the control group. Data were obtained from medical records and routine patient visits and analyzed using SPSS version 29.0 using univariate analysis, the Shapiro-Wilk test, and the Mann-Whitney test. The results showed that outpatients with Type 2 Diabetes Mellitus at Bhakti Kartini Hospital were predominantly women aged 31–69, with a high school education, self-employment, duration of diabetes ≤ 5 years, and hypertension as the most common comorbidity. The analysis revealed a significant difference in quality of life between the control and intervention groups, indicating that pharmacist counseling plays a role in improving patients' quality of life. Furthermore, demographic factors did not significantly correlate with quality of life, suggesting that improvements in patient quality of life are more influenced by pharmacist counseling interventions and optimal therapy management.